Pengaruh Tingkat Suku Bunga dan Jangka Waktu terhadap Kredit Macet (Studi Kasus pada Koperasi Syariah Masyarakat Kertasinduyasa) - Sholikha Puji Astuti; Andi Yulianto; Dumadi; Amelia Sholehah; Maftukhin (Journal of Accounting and Finance (JACFIN), 2019)
The purpose of this research is to determine the effect of interest rates and term to non performing loans. This research was conducted in the Koperasi Syariah Masyarakat Kertasinduyasa with a population of 50 respondents. The data collection method in this research is done by distributing questionnaires to respondents who have non performing loan in the cooperative. The data analysis used was an instrument test which included validity test and realibility test, classic assumption test which include normality test, multicollinearity test, and heteroscedasticity test, hypothesis test which include t test and f test, and determination correlation test. From the results of the test conducted, it is concluded that there is a significant influence on the variable interest rate on the non performing loan variable with a significance value of 0,007 < 0,05, while the time period variable has no significant effect on the non performing loan variable with a significance value of 0,872 > 0,05.